Thermal design and optimization of HIAF′s medical isotope target under extreme heat flux based on a two-way fluid–structure interaction model - Xin Li; Heng Zhang; Zihao Zhang; Jianrong Zhang; Qingfeng Tang; Wei Wang; Yucui Gao; Lei Yang; Yaling Zhang (Annals of Nuclear Energy, 2026)

Low-lethal and intergenerational effects of broflanilide on the diamondback moth, Plutella xylostella (L.) - Kunkun Wang; Qiqi Zhao; Chenyao Yang; Chen Shen; Qichao Zhang; Renwen Zheng; Pei Liang; Qingfeng Tang (Pesticide Biochemistry and Physiology, 2026)

An onboard ultra-rapid orbit determination strategy for LEO satellite utilizing spaceborne GNSS data - Peng Luo; Yezhi Song; Xiaogong Hu; Qingfeng Wu; Jianhua Yang; Kai Li; Chengpan Tang; Changshao Chen (Advances in Space Research, 2026)

A star’s death by a thousand cuts: the runaway periodic eruptions of AT2023uqm - Yibo Wang; Tinggui Wang; Shifeng Huang; Jiazheng Zhu; Ning Jiang; Wenbin Lu; Rongfeng Shen; Shiyan Zhong; Dong Lai; Yi Yang; Xinwen Shu; Tianyu Xia; et al. (Science Bulletin, 2026)

SfIML-1 interacts with integrin β5 to mediate fungal conidial adhesion and immune activation in Spodoptera frugiperda - Fang-Fang Liu; Qi-Gui Gao; Yue Sun; Chao-Peng Liang; Hai-Yan Ren; Qingfeng Tang; Liang Wen; Bang-Xian Zhang; Xiang-Jun Rao (Pesticide Biochemistry and Physiology, 2026)

Inferring irrigation regimes and sunshine duration from the distribution and spectral characteristics of farmland microplastics - Hangzheng Zhao; Xu Han; Changming Cao; Ziyi Zan; Bo-Tao Zhang; Jiamin Wang; Qingfeng Tang; Weifeng Yue; Yan Liu (Environmental Pollution, 2026)

Study on the effects of ultraviolet inactivation in the process of gynogenetic development of grass carp eggs induced by mirror carp sperm - Wangchao He; Yu Sun; Kuo Chen; Junwen Liang; Binchao Liang; Xinyan Zhu; Qingfeng Liu; Yang Chen; Jialin Tang; Fuzhong Yang; Chun Zhang; Bo Chen; et al. (Aquaculture, 2026)

Chloride ions accelerated the removal of naproxen in Cu(II)/peracetic acid system: Promotion of copper cycling through the formation of copper-chloride complexes - Chenyu Tang; Jianying Wu; Yao Huang; Jing Zou; Bo Sun; Minfeng Wang; Qingfeng Cheng; Haoqiang Tan; Qingsong Li (Water Research, 2026)

Enhanced removal of organic pollutants and effective suppression of chlorinated/brominated by-products in heat/peroxymonosulfate system by adding sodium percarbonate - Yao Huang; Chenyu Tang; Bingyu Lu; Jianhang Li; Lukai Zhuang; Minfeng Wang; Haoqiang Tan; Qingfeng Cheng; Qingsong Li; Bo Sun; Jing Zou (Journal of Environmental Chemical Engineering, 2026)

The effects of endophytic fungal metabolites from Conyza blinii on antioxidant capacity and healthspan in Caenorhabditis elegans - Yixuan Qi; Yujie Jia; Yixin Chen; Hongying Zhu; Yirong Xiao; Zhao Chen; Limin Su; Xinyu Zhang; Wenrong Zhao; Zhengjiang Li; Youpeng Tuo; Tongliang Bu; et al. (Natural Product Research, 2026)

Near-Earth Asteroid orbit determination with Physics-Informed Extreme Learning Machine - Xiuyu Chen; Kai Tang; Qingfeng Zhang; Zhenliang Tian; Yong Yu (Icarus, 2026)

MnO2-resistant ABTS spectrophotometry for trace permanganate - Chenyu Tang; Jianying Wu; Yao Huang; Jing Zou; Xuewei Yu; Bo Sun; Zhongda Yan; Haoqiang Tan; Qingfeng Cheng; Jun Ma (ENGINEERING Environment, 2026)

Polyethylene microplastics specifically drive the dissemination of ARGs: Mechanisms involving microbial community restructuring and horizontal gene transfer - Xionghao Hu; Kehong Yu; Beibei Chai; Qingfeng Tang; Xia Gao; Jiamin Wang; Zhaoyang Yan; Yang Li; Lei Zhang; Chao Wang; Xiaohui Lei; Bin Chen; et al. (Science of The Total Environment, 2026)

Mechanisms of growth enhancement in Tartary buckwheat by endophytic fungi: a transcriptomic and metabolomic insight - Qiqi Xie; Yujie Jia; Jiwen Tao; Tongliang Bu; Xinyu Zhang; Yirong Xiao; Qingfeng Li; Zizhong Tang; Lu Zhang; Gonghong Li; Junhua Liao (Plant and Soil, 2026)

Facilitating redox cycles of copper species by peroxydisulfate in the copper-catalyzed Fenton-like system for enhanced oxidation of organic contaminants - Bingyu Lu; Jianying Wu; Chenyu Tang; Jing Zou; Bo Sun; Minfeng Wang; Qingfeng Cheng; Haoqiang Tan; Qingsong Li; Jun Ma (Water Research, 2026)

pH-dependent synergistic enhancement of U(VI) transport by phosphate and bentonite colloids - Yanhui Wang; Qi Tan; Yujie Hong; Jingli Xie; Qingfeng Tang; Zhiwei Niu; Duoqiang Pan; Wangsuo Wu; Zhen Xu (Journal of Hazardous Materials, 2026)

Macro‐Hybrid and Micro‐Hybrid of Fish - Qizhi Liu; Anmin Liao; Min Tao; Qinbo Qin; Kaikun Luo; Chun Zhang; Shi Wang; Yi Zhou; Fangzhou Hu; Yude Wang; Chang Wu; Wuhui Li; et al. (Reviews in Aquaculture, 2026)
This study reviews the progress in fish breeding, focusing on distant hybridization and gynogenesis, and introduces the theory of macro‐hybrid and micro‐hybrid. The macro‐hybrid refers to the allo‐progeny derived from distant hybridization, including the allo‐progenies. The micro‐hybrid refers to the auto‐progenies derived from distant hybridization or heterologous sperm‐induced gynogenesis, which possess a genome derived predominantly from the maternal but contain DNA fragments originating from the paternal. Macro‐hybrids induce significant phenotypic changes, while micro‐hybrids improve growth rate and stress resistance. Both hybridization and gynogenesis exhibit high selective pressure. This review elucidates how selective pressures (homozygosity + heterologous sperm + cold/heat shock) of the heterologous sperm‐induced gynogenesis contribute to the generation of effective genetic variations. The study also presents the technologies of macro‐hybrid and micro‐hybrid. In macro‐hybrids of distant hybridization, parental chromosome numbers are closely matched, enabling the formation of fertile allo‐diploid and allo‐tetraploid strains. In micro‐hybrid of distant hybridization, equal or differing chromosome numbers between parents yield fertile auto‐tetraploid and auto‐diploid strains. In micro‐hybrid of heterologous sperm‐induced gynogenesis, equal or different chromosome numbers between parents yield auto‐diploid strains. The integration of heterologous sperm‐induced gynogenesis, back‐cross, and self‐cross strategies can address the issue of all‐female progeny resulting from gynogenesis. A series of auxiliary breeding techniques is established to support the macro‐hybrid and micro‐hybrid breeding. Case studies of superior fish strains developed through macro‐hybrid and micro‐hybrid breeding are presented. The establishment of macro‐hybrid and micro‐hybrid theory and breeding technologies holds significant value for fish breeding.

Cover Image - Qizhi Liu; Anmin Liao; Min Tao; Qinbo Qin; Kaikun Luo; Chun Zhang; Shi Wang; Yi Zhou; Fangzhou Hu; Yude Wang; Chang Wu; Wuhui Li; et al. (Reviews in Aquaculture, 2026)
The cover image is based on the article Macro‐Hybrid and Micro‐Hybrid of Fish by Shaojun Liu et al., https://doi.org/10.1111/raq.70106 . image

Efficient removal of Pb2+ by iron-doped hydroxyapatite: Synthesis, adsorption, kinetics and mechanisms - Yan Li; Yuxia Zhong; Hang Lei; Qingfeng He; Fengchu Liao; Sisi Tang; Mengdi Liu; Yue-Fei Zhang (Environmental Research, 2025)

Dual-responsive carboxymethyl cellulose-based hydrogel sensor with antibacterial activity for wound monitoring and infected wound repair - Zhengjie Yu; Fanwei Zeng; Yuejin Cai; Zijie Wang; Ze Chen; Ruizi Wang; Qingfeng Sun; Xiaodong Tang; Xiaoping Shen; Hongxia Xie (Chemical Engineering Journal, 2025)

Unraveling Eu(III) immobilization and cotransport risk with Bacillus subtilis from colloid aggregation, biosorption, and biomineralization - Zhen Xu; Qingfeng Tang; Yanhui Wang; Yuan Chen; Zhiwei Niu; Duoqiang Pan; Wangsuo Wu (Chemical Engineering Journal, 2025)

Nitrogen-doped graphite supported cobalt nanoparticles as excellent ORR/OER/HER trifunctional electrocatalysts - Wenxuan Fan; Xiangmei Tang; Qingfeng Yi; Guang Li (Fuel, 2025)

Ultrasound triggered spatial-temporal NO gas release to enhance sonodynamic therapy and immune checkpoint blockade therapy against pancreatic cancer - Wanrui Shi; Jianfeng Zhang; Ruiqi Wu; Shiti Shama; Shi Tan; Heng Xue; Yan Sun; Qingshuang Tang; Suhui Sun; Rui Tang; Guotao Feng; Xiaoda Li; et al. (Chemical Engineering Journal, 2025)

Bacillus subtilis morphology and bentonite colloids govern Eu(III) transport in quartz sand: Mechanisms and machine learning insights - Qingfeng Tang; Zhengye Feng; Yanhui Wang; Xiaoyan Wei; Duoqiang Pan; Wangsuo Wu; Zhen Xu (Journal of Hazardous Materials, 2025)

Sb3+-doped terbium-based metal halide with efficient dual band emission for ratiometric temperature sensing - Zhe Tang; Xiaochen Wang; Shuyue Wang; Maria Syskaki; Qingfeng Wei; Binbin Fan; Chenxin Fan; Dandan Luo; Tianxin Bai; Junsheng Chen (Chemical Engineering Journal, 2025)

Physiological and transcriptomic responses of fall armyworm, Spodoptera frugiperda to host-plant switching - Jun Peng; Renwen Zheng; Jinyuan Zhao; Jinhui Zhang; Qianqian Li; Dongyan Huang; Xin Zhou; Lijuan Liu; Zhuocong Li; Xiaoman Ning; Sihan Lu; Qingfeng Tang (Journal of Pest Science, 2025)

An occupational health assessment of dinotefuran exposure in greenhouse vegetable workers: Metabolomic profiling and toxicokinetic analysis - Jiamin Li; Hao Zhang; Ke Zhao; Chengcheng Han; Changjian Li; Lei Fang; Haiyong Jia; Yong Wang; Hanqiu Tang; Qingfeng Zhai; Peng Xue (Journal of Hazardous Materials, 2025)

Evaluation of slag and tannery sludge based geopolymer after thermal exposure: Properties, phase transformation and Cr leaching behavior - Jialin Chen; Jingfei Zhou; Shoukai Chen; Haibo Shi; Qingfeng Hu; Yingdong Tang (Journal of Cleaner Production, 2025)

Effects of dietary rumen-degradable protein on the growth performance, energy, and nitrogen metabolism of dairy buffalo heifers - Qingfeng Tang; Pengcheng Shao; Chongli Wen; Zeming Bu; Guangsheng Qin; Yali Huang; Yuhong Pan; Zhipei Li; Kelong Wei; Shulu Li; Bishi Lan; Huapei Zhong; et al. (Tropical Animal Health and Production, 2025)

Gut bacteria of the fall armyworm, Spodoptera frugiperda, promote host resistance against the toxic effects of lufenuron - Qianqian Li; Renwen Zheng; Jinyuan Zhao; Sihan Lu; Yue Liu; Dongyan Huang; Jinhui Zhang; Lijuan Liu; Xin Zhou; Qingfeng Tang (Journal of Pest Science, 2025)

The crucial role of protein corona in mediating the colloid stability and co-transport behaviors in saturated quartz columns - Zhen Xu; Qingfeng Tang; Qi Tan; Zhengye Feng; Yanhui Wang; Hui Zhang; Duoqiang Pan; Wangsuo Wu (Chemosphere, 2025)

Mechanistic model for the cotransport of colloids and radionuclides in saturated porous systems based on the interaction forces between colloids - Qi Tan; Qingfeng Tang; Xinyi Shi; Hongjie Zhao; Shuyang Li; Yuan Chen; Xiaoyan Wei; Zhen Xu; Duoqiang Pan; Wangsuo Wu (Applied Geochemistry, 2025)

Alterations in microbial community structures and metabolic function in soil treated with biological and chemical insecticides - Renwen Zheng; Jun Peng; Qianqian Li; Yue Liu; Dongyan Huang; Yangjunlu Sheng; Cui Liu; Lei Qi; Nemat O. Keyhani; Qingfeng Tang (Pesticide Biochemistry and Physiology, 2025)

El Niño-Southern Oscillation signals imprinted in stalagmite δ18O from 2005 to 2017 - Jianshun Chen; Yijia Liang; Kan Zhao; Yongjin Wang; Zhenqiu Zhang; Fucai Duan; Jingwei Zhang; Qingfeng Shao; Junji Zhu; Shaohua Yang; Lian Tang; Yuqing Wang; et al. (Quaternary International, 2025)

The Research Advances in Distant Hybridization and Gynogenesis in Fish - Qizhi Liu; Shi Wang; Chenchen Tang; Min Tao; Chun Zhang; Yi Zhou; Qinbo Qin; Kaikun Luo; Chang Wu; Fangzhou Hu; Yude Wang; Qingfeng Liu; et al. (Reviews in Aquaculture, 2025)
Distant hybridization and gynogenesis are two prevalent breeding techniques for fishes. Drawing from the research achievements of our team and the existing literature, we summarize the reproductive traits and genetic features of fishes derived from distant hybridizations and gynogenesis, and we deduce the fundamental mechanisms of these two methods and compare them, discerning their common and different characteristics. Both distant hybridization and gynogenesis techniques can alter genotypes and phenotypes, thus establishing them as significant breeding methods. Additionally, the genetic principles and the basic biological characteristics of distant hybridization and gynogenesis in fish have been inferred. We propose the concepts of macro‐hybrid and micro‐hybrid based on extensive experimental findings from fish distant hybridizations and gynogenesis. The term “macro‐hybrid” refers to offspring from distant hybridization that possess two distinct subgenomes, each inherited from one of the two parental species, such as allodiploid and allotetraploid lineages. The concept of “micro‐hybrid” refers to offspring, including autodiploid and autotetraploid lineages, as well as those resulting from artificial gynogenesis, whose genome almost originates solely from the maternal parent but in which certain DNA fragments derived from the paternal parent insert. Distant hybridization and gynogenesis are vital techniques in fish genetics, breeding, and evolution. We highlight the prospective paths for research and application of distant hybridization and gynogenesis in fishes.

A preliminary result for centralized autonomous orbit determination of gnss constellation and lunar satellite based on inter-satellite link measurements - Peng Luo; Ye-Zhi Song; Jianhua Yang; Xiaogong Hu; Chengpan Tang; Kai Li; Qingfeng Wu (GPS Solutions, 2024)

Microplastics increase the microbial functional potential of greenhouse gas emissions and water pollution in a freshwater lake: A metagenomic study - Tianyu Zhuo; Kehong Yu; Beibei Chai; Qingfeng Tang; Xia Gao; Jiamin Wang; Lixin He; Xiaohui Lei; Yang Li; Yuan Meng; Lifeng Wu; Bin Chen (Environmental Research, 2024)

Construction of Remote Sensing Quantitative Model for Biomass of Deciduous Broad-Leaved Forest in Mazongling Nature Reserve Based on Machine Learning - Xuehai Tang; Dagui Yu; Haiyan Lv; Qiangxin Ou; Meiqin Xie; Peng Fan; Qingfeng Huang (Journal of the Indian Society of Remote Sensing, 2024)
As an important forest type, deciduous broad-leaved forest is crucial for estimating forest carbon sequestration capacity and evaluating forest carbon balance. This study focuses on the natural deciduous broad-leaved forest of Mazongling Nature Reserve in Jinzhai County of China. WorldView-2 images were selected as data source. 36 candidate factors including vegetation indices, texture features, and topographic factors were used for modelling. Three machine learning algorithms (i.e., random forest, k-nearest neighbor, and artificial neural network) were used to establish the optimal quantitative retrieval model for natural deciduous broad-leaved biomass. Results showed that the ANN model was the best predictor with R 2 = 0.69 and RMSE = 31.53 (Mg·ha −1 ). Combining the ANN model with the complete spatial coverage of remote sensing data, we developed a distribution map of natural deciduous broad-leaved biomass in the Mazongling forest farm. The estimated average biomass of the study area was 90.34 ± 47.96 Mg·ha −1 . In addition, the influence of light saturation on model accuracy is also discussed. This study confirms that remote sensing data in temporal and spatial space can improve the model estimation accuracy.

Coupled ESR and U-series dating of the northernmost evidence of Gigantopithecus from Jianshi Longgudong site, China - Fei Han; Jean-Jacques Bahain; Qingfeng Shao; Pierre Voinchet; Fangfang Tang; Mi Zhou; Manchen Huang; Gongming Yin (Quaternary Geochronology, 2024)

Millennial to orbital scale Indian summer monsoon evolution inferred from grain size end-members in Tengchongbeihai wetland, southwestern China - Dongliang Ning; Xiayun Xiao; Suqin Tang; Yuchen Xu; Xiang Kuai; Ying Ge; Jianan Zheng; Longjuan Cheng; Dejun Wan; Qingfeng Jiang; Yanling Li (Quaternary Science Reviews, 2024)

Identification of sex locus and a male-specific marker in blunt-snout bream (Megalobrama amblycephala) using a whole genome resequencing method - Ming Wen; Siyu Wang; Chunchun Zhu; Yuxin Zhang; Zheng Liu; Chang Wu; Shi Wang; Yude Wang; Li Ren; Min Tao; QinBo Qin; Chun Zhang; et al. (Aquaculture, 2024)

Estimation of the Relative Chlorophyll Content of Carya illinoensis Leaves Using Fractional Order Derivative of Leaf and Canopy Scale Hyperspectral Data - Jiajia Xu; Genshen Fu; Lipeng Yan; Lei Yu; Fan Kuang; Qingfeng Huang; Xuehai Tang (Journal of Soil Science and Plant Nutrition, 2024)
Chlorophyll is a crucial physiological and biochemical indicator that impacts plant photosynthesis, accumulation of photosynthetic products, and final yield. The measurement and analysis of chlorophyll content in plants can provide valuable insights into their nutritional status and overall health. The non-destructive and efficient estimation of relevant plant physiological and biochemical indicators using hyperspectral technology can provide a reliable method for collecting data on nutrient levels and health status during plant growth and development. Fifty-three Carya illinoensis plants of Jiande and Changlin series known for their exceptional qualities and significant economic benefits were used as the research object for collecting their leaf and canopy hyperspectral data. Firstly, fractional order derivative (FOD) was used for spectral preprocessing. Secondly, the spectral response relationship between spectrum and relative chlorophyll content (soil and plant analyzer development, SPAD) was explored by combining single-band and two-band spectral index (normalized difference spectral index, NDSI). The correlation coefficient of Pearson correlation analysis was used to estimate the linear correlation between variables. Finally, the correlation between the spectral feature variables and SPAD was analyzed and calculated. Top 10 absolute values of the correlation coefficients were screened out as modeling variables. eXtreme gradient boosting (XGBoost) machine learning algorithm was used to construct the optimal estimation model of SPAD of Carya illinoensis leaves. Results showed that the correlation between leaf and canopy spectrum after FOD pretreatment and SPAD was substantially improved, compared with raw spectrum. FOD combined with leaf and canopy NDSI was more effective than single band in improving the correlation between spectral characteristics and target components, which was increased by 0.166 and 0.338, respectively. The leaf spectrum could estimate SPAD more accurately than that of canopy spectrum. The optimal SPAD model was the 0.5th-order derivative transformation combined with two-band leaf spectral index (NDSI) model. The R 2 P was 0.788, and the RMSEP was 0.842 in prediction set. On one hand, this study confirms the feasibility of rapid and non-destructive estimation of SPAD of Carya illinoensis leaves using hyperspectral technology. On the other hand, FOD combined with two-band spectral indices can significantly improve the response relationship between spectral characteristics and target variables, enrich hyperspectral data processing methods, and propose a novel approach for the detection of plant nutrient level and health.

Insight into Impact of Phosphate on the Cotransport and Corelease of Eu(III) with Bentonite Colloids in Saturated Quartz Columns - Qingfeng Tang; Zhen Xu; Qi Tan; Xingyi Shi; Wangsuo Wu; Duoqiang Pan (Journal of Hazardous Materials, 2024)

Spatial pattern and cause of centennial-scale hydroclimatic variability over eastern China during the last millennium - Jian-Jun Yin; Zhijun Wang; Wenqiang Shi; Qingfeng Shao; Xia Wu; Wei Tang; Yuan Ma (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Ensemble data assimilation for open channel water level forecasting under flow disturbances: A synthetic data study - Lingzhong Kong; Ruibin Chen; Hongwu Tang; Saiyu Yuan; Qian Yang; Qingfeng Ji (Journal of Hydrology, 2023)

Mechanistic insights into gel formation of egg-based yoghurt: The dynamic changes in physicochemical properties, microstructure, and intermolecular interactions during fermentation - Jianwei Zang; Xiaoyang Pan; Yuanyuan Zhang; Yonggang Tu; Haixia Xu; Daobang Tang; Qingfeng Zhang; Jiguang Chen; Zhongping Yin (Food Research International, 2023)

Insecticidal potential of a Consolida ajacis extract and its major compound (ethyl linoleate) against the diamondback moth, Plutella xylostella - Jun Peng; Zihan Chen; Xueqian Chen; Renwen Zheng; Sihan Lu; Muhammad Seyab; Fan Yang; Qianqian Li; Qingfeng Tang (Pesticide Biochemistry and Physiology, 2023)

Hydrostatic pressure drives microbe-mediated biodegradation of microplastics in surface sediments of deep reservoirs: Novel findings from hydrostatic pressure simulation experiments - Kehong Yu; Beibei Chai; Tianyu Zhuo; Qingfeng Tang; Xia Gao; Jiamin Wang; Lixin He; Xiaohui Lei; Bin Chen (Water Research, 2023)

Advances in the formation mechanism, influencing factors and applications of egg white gels: A review - Jianwei Zang; Yuanyuan Zhang; Xiaoyang Pan; Dayong Peng; Yonggang Tu; Jiguang Chen; Qingfeng Zhang; Daobang Tang; Zhongping Yin (Trends in Food Science & Technology, 2023)

The Tartary buckwheat bHLH gene ALCATRAZ contributes to silique dehiscence in Arabidopsis thaliana - Wenjun Sun; Ying Chen; Jing Zeng; Chenglei Li; Min Yao; Moyang Liu; Zhaotang Ma; Li Huang; Jun Yan; Junyi Zhan; Hui Chen; Tongliang Bu; et al. (Plant Science, 2023)

Consolidating the gelling performance of myofibrillar protein using a novel OSA-modified-starch-stabilized Pickering emulsion filler: Effect of starches with distinct crystalline types - Qingling Wang; Yi Luan; Ziwei Tang; Zhikun Li; Chen Gu; Rui Liu; Qingfeng Ge; Hai Yu; Mangang Wu (Food Research International, 2023)

Mechanism of molecules crosstalk and the critical role of jasmonic acid on triterpenoid synthesis in Cyclocarya Paliurus cells under Aspergillus niger elicitor - Meng Wang; Daobang Tang; Qiongqiong Xiong; Jiguang Chen; Xiaoxiang Xu; Qingfeng Zhang; Jingen Li; Xiangju Zhou; Zhongping Yin (Journal of Plant Biochemistry and Biotechnology, 2022)

An improved hybrid bream derived from a hybrid lineage of Megalobrama amblycephala (♀)×Culter alburnus (♂) - Dingbin Gong; Min Tao; Lihui Xu; Fangzhou Hu; Zehong Wei; Shi Wang; Yude Wang; Qingfeng Liu; Chang Wu; Kaikun Luo; Chenchen Tang; Rong Zhou; et al. (Science China Life Sciences, 2022)

Development of suspension culture technology and hormone effects on anthocyanin biosynthesis for red Cyclocarya paliurus cells - Yuan Liu; Qi Liang; Daobang Tang; Yuqin Chen; Jianwei Zang; Wenjia Zhao; Jiguang Chen; Qingfeng Zhang; Zhongping Yin (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Fifty years of Quaternary palynology in the Tibetan Plateau - Lingyu Tang; Caiming Shen; Houyuan Lu; Chuanhai Li; Qingfeng Ma (Science China Earth Sciences, 2021)

Alpha 1-antichymotrypsin may be a biomarker for the progression of amnestic mild cognitive impairment - Shunjie Liu; Junhao Pan; Ke Tang; Qingfeng Lei; Lu He; Xiaodong Cai; Zhong Li (Acta Neurologica Belgica, 2021)

Extraction Optimization and Characterization of Gelatin from Half-Smooth Tongue Sole ( Cynoglossus semilaevis Gunther) Skin - Yanjie Li; Chunming Tang; Qingfeng He; Xiaodan Li; Ailin Zhang (Journal of Aquatic Food Product Technology, 2019)

Geochemistry of pyrite and chalcopyrite from an active black smoker in 49.6°E Southwest Indian Ridge - Bo Yuan; Yaomin Yang; Hongjun Yu; Yuexia Zhao; Qingfeng Ding; Jichao Yang; Xin Tang (Marine Geophysical Research, 2018)

Comparison of a fuzzy control and the data-driven model for flood forecasting - Yixiang Sun; Deshan Tang; Yifei Sun; Qingfeng Cui (Natural Hazards, 2016)

Daidzein Induced Apoptosis via Down-Regulation of Bcl-2/Bax and Triggering of the Mitochondrial Pathway in BGC-823 Cells - Shuyao Tang; Jing Hu; Qingfeng Meng; Xuesong Dong; Kaifu Wang; Yuebin Qi; Chao Chu; Xiaochuan Zhang; Limin Hou (Cell Biochemistry and Biophysics, 2013)